Sport Development via Sustainable Urban Land Use - The Case of Győr, Hungary - Szaloki, Richard; Szakonyi, Petra (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
This study presents an overview of the key sports developments in Győr over the past decade, emphasizing the significance of sustainable urban land use, particularly in the context of brownfield rehabilitation and comprehensive city development. Sustainable land use plays a crucial role in influencing economic, social, and environmental dynamics and aligns with the European Union's goal of achieving no net land take by 2050. In Hungary, this objective is also part of the national development strategy. Recent legislative changes, including the Architecture Act XXIII of 2023 and impending regulations for Spatial Planning and Building Requirements, underscore the focus on brownfield rehabilitation and the protection of green spaces. The paper discusses notable sports developments in Győr as well as those in other European cities, such as London and Paris. It explores the challenges faced by various investment types and identifies future opportunities for sustainable urban land use. Additionally, the study aims to highlight the social, economic, and environmental aspects of these sports investments.